2015
DOI: 10.1093/nar/gkv505
|View full text |Cite
|
Sign up to set email alerts
|

ATP-dependent motor activity of the transcription termination factor Rho fromMycobacterium tuberculosis

Abstract: The bacterial transcription termination factor Rho—a ring-shaped molecular motor displaying directional, ATP-dependent RNA helicase/translocase activity—is an interesting therapeutic target. Recently, Rho from Mycobacterium tuberculosis (MtbRho) has been proposed to operate by a mechanism uncoupled from molecular motor action, suggesting that the manner used by Rho to dissociate transcriptional complexes is not conserved throughout the bacterial kingdom. Here, however, we demonstrate that MtbRho is a bona fide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(68 citation statements)
references
References 56 publications
(144 reference statements)
5
63
0
Order By: Relevance
“…It was hypothesized that the N-terminal domain might be responsible for the apparent dispensability of ATP hydrolysis. In contrast, a second study found ATP hydrolysis to be essential for transcription termination by M. tuberculosis Rho in vitro 26. To evaluate importance of ATP binding to Rho for growth of M. tuberculosis we mutated the amino acids D440, R541 and E386 to N440, A541 and A386.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was hypothesized that the N-terminal domain might be responsible for the apparent dispensability of ATP hydrolysis. In contrast, a second study found ATP hydrolysis to be essential for transcription termination by M. tuberculosis Rho in vitro 26. To evaluate importance of ATP binding to Rho for growth of M. tuberculosis we mutated the amino acids D440, R541 and E386 to N440, A541 and A386.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Rho of M. tuberculosis is predicted to be essential for growth2425, but is poorly inhibited by BCM (ref. 26), which suggests that targeting mycobacterial Rho could allow development of genus-specific antibiotics.…”
mentioning
confidence: 99%
“…Critical, direct molecular interactions between Spt5 and RNAP have been identified in both Bacteria and Archaea, and the conservation of RNAP and Spt5 infers that these same interactions are used in Eukarya. Briefly, a hydrophobic depression on the NGN domain interacts with the mobile clamp domain of RNAP, with additional interactions between the NGN domain and RNAP jaw domain likely fixing the location of the clamp domain in a closed configuration (81). Spt5 interaction with RNAP is not necessary for productive and processive elongation in vitro, but the interaction does increase the total output of transcription systems (1).…”
Section: Regulation Of Transcription Elongationmentioning
confidence: 99%
“…Transcription is highly regulated, and the transcription cycle is typically demarcated into three phases: initiation, elongation, and termination (9)(10)(11)(12)(13) (Fig. 1).…”
Section: The Archaeal Transcription Cyclementioning
confidence: 99%
“…Bioinformatic analyses reveal some potential targets that remain to be more fully evaluated, but there are no easily identified homologues of known eukaryotic or bacterial termination factors. Two well-studied transcription bacterial termination factors, Rho and Mfd (13,(146)(147)(148)(149)(150), lack clear homologues in archaeal genomes, but there are hints that analogous activities may be present in archaeal species. Rho is a homohexamer helicase that represses phage transcription and mediates polar repression of downstream genes when transcription and translation become uncoupled (142,(151)(152)(153).…”
Section: Identification Of Factor-dependent Terminationmentioning
confidence: 99%